Subject-Oriented Approach in the Professional Formation of the Future Music Teacher - Karkina, Svetlana V.; Fajzrahmanova, Lyalya T.; Gluzman, Aleksandr V. (Journal of History Culture and Art Research, 2017)
The article deals with the possibilities of introducing a subject-oriented approach into the practice of professional education of the future music teacher. Particular attention is paid to the forms and methods used in this field, as well as to the conditions of the modern cultural environment, which allows for the free self-realization of the individual in accordance with his subject needs. Subject-oriented approach is the practice-oriented research. The study identified a number of the most significant components in the preparation of a music teacher, such as individual forms of studies and a number of special methods, which include the method of artistic associations, verbal "allegories", metaphors, the method of heuristic tasks for mastering creative activities. The openness of the musical and pedagogical system has great importance in its ability to respond to changes in the music and educational environment, which includes educational institutions and various cultural institutions: theaters, concert halls, orchestral and choir groups. All that conditions are necessary to ensure the possibility of creative self-realization and self-actualization of future music teachers.